Evaluasi Kemampuan Menulis Teks Berita Siswa Kelas VII SMP Negeri 3 Purwokerto: Pendekatan Struktur Teks Van Dijk - Zahra Amalia Utami; Memet Sudaryanto; Nur Indah Sholikhati (Universitas Nahdlatul Wathan Mataram, 2026)
Studies on student-written news texts tend to focus on language errors, whereas research that systematically examines text structure based on van Dijk’s model remains relatively limited. This study aims to describe the structure of news texts written by seventh-grade students at SMP Negeri 3 Purwokerto based on macro-structure, superstructure, and micro-structure aspects. This study employs a qualitative approach using a descriptive method. The research data consisted of ten news texts written by students, obtained through documentation and analyzed using the model by Miles, Huberman, and Saldana (2014). The results indicate that regarding macro-structure, 9 out of 10 texts (90%) contained clear and relevant topics, including themes such as traffic accidents, natural disasters, environmental issues, and crime. In terms of superstructure, 7 out of 10 students (70%) were able to compose news texts coherently in accordance with journalistic conventions (headline, lead, body, and conclusion), although 3 texts still featured a concluding section that was persuasive and opinionated. Regarding microstructure, the semantic, stylistic, and rhetorical aspects were each met by 9 out of 10 students (90%), while syntax was the weakest aspect, with only 8 students (80%) meeting it; the main weaknesses were found in the inefficient use of compound sentences, the placement of conjunctions at the beginning of sentences, and punctuation errors. These findings indicate that students possess the ability to develop themes and organize news structures but still require reinforcement in linguistic aspects. This study contributes to demonstrating the application of van Dijk’s model in analyzing student texts and provides practical implications for teaching news writing in schools.